Pre- and Interhospital Workflow Times for Patients With Large Vessel Occlusion Stroke Transferred for Endovasvular Thrombectomy - van Meenen, Laura C. C.; Riedijk, Frank; Stolp, Jeffrey; van der Veen, Bas; Halkes, Patricia H. A.; van der Ree, Taco C.; Majoie, Charles B. L. M.; Roos, Yvo B. W. E. M.; Smeekes, Martin D.; Coutinho, Jonathan M. (Frontiers in Neurology, 2021)
Background Patients with large vessel occlusion (LVO) stroke are often initially admitted to a primary stroke center (PSC) and subsequently transferred to a comprehensive stroke center (CSC) for endovascular thrombectomy (EVT). This interhospital transfer delays initiation of EVT. To identify potential workflow improvements, we analyzed pre- and interhospital time metrics for patients with LVO stroke who were transferred from a PSC for EVT. Methods We used data from the regional emergency medical services and our EVT registry. We included patients with LVO stroke who were transferred from three nearby PSCs for EVT (2014-2021). The time interval between first alarm and arrival at the CSC (call-to-CSC time) and other time metrics were calculated. We analyzed associations between various clinical and workflow-related factors and call-to-CSC time, using multivariable linear regression. Results We included 198 patients with LVO stroke. Mean age was 70 years (±14.9), median baseline NIHSS was 14 (IQR: 9-18), 136/198 (69%) were treated with intravenous thrombolysis, and 135/198 (68%) underwent EVT. Median call-to-CSC time was 162 minutes (IQR: 137-190). In 133/155 (86%) cases, the ambulance for transfer to the CSC was dispatched with the highest level of urgency. This was associated with shorter call-to-CSC time (adjusted β [95% CI]: -27.6 minutes [-51.2 to -3.9]). No clinical characteristics were associated with call-to-CSC time. Conclusion In patients transferred from a PSC for EVT, median call-to-CSC time was over 2.5 hours. The highest level of urgency for dispatch of ambulances for EVT transfers should be used, as this clearly decreases time to treatment.